Proximal Over-resection During Femoral Osteochondroplasty Negatively Affects The Distractive Stability Of The Hip Joint. Issue 3 (27th March 2020) - Lazaro, Lionel E.; Lim, Daniel P.; Nelson, Trevor; Eberlein, Samuel; Banffy, Michael B.; Metzger, Melodie
Objectives: Hip microinstability is an increasingly recognized source of hip pain and disability. Femoral osteochondroplasty is usually performed with direct visualization through an arthroscope, assisted with repeated fluoroscopic imaging. However, a two-dimensional representation of a three-dimensional structure is misleading and may compromise the precision of the planned osteochondroplasty. The resection can occasionally extend proximally into the Femoral Head diminishing the articular surface area available for suction seal. The purpose of this study was to determine whether proximal over-resection decreases the rotational and distractive stability of the hip joint. Methods: Six hemi-pelvises were repeatedly tested in the following conditions: (a) intact, (b) T-capsulotomy, (c) Osteochondroplasty to the physeal scar, followed by (d) 5mm and (e) 10mm proximal extension. The pelvis was secured to a metal plate and the femur was potted and attached to a multi-axial hip jig. Specimens were axially distracted with a load from 0-150N followed by 5Nm of internal and external torque at 0o, 15o, 30o, 60o, 90o of flexion. Displacement/rotation was recorded using a 3D motion tracking system. Repeated measures ANOVA was used with significance set at p<0.05. Results: Proximal extension of the resection by 5mm and 10mm increased axial instability at every angle of flexion tested, with the greatest increase observed at higher angles of flexion, p<0.05. T-capsulotomy alone increased both internal and external rotation at all angles of flexion, p<0.05. Subsequent resection and extension of the resection did not significantly increase rotational instability compared to the capsulotomy state. Conclusion: Extending the osteochondroplasty proximally into the femoral head compromises the distractive stability of the hip joint, but doesn't not effect hip rotational stability. Clinically, this highlights the importance of accuracy when performing femoral osteochondroplasty to minimize proximal extension that may increase iatrogenic instability of the hip joint, leading to reduced post-operative outcomes. :